Peran Orang Tua, Atlet, Klub, Masyarakat, KONI, dan Pemerintah dalam Perkembangan Olahraga Senam Lantai (Artistik) di Kabupaten Rembang (Indonesian Journal for Physical Education and Sport, 2021)
ABSTRACT Dewi Wahyu Riana. 2021. The Role of Parents, Athletes, Clubs, Communities, Koni, and The Government in the Development of Floor Gymnastics (Artistic) in Rembang Regency. Final project, Physical Education, Health and Recreation, Faculty of Sports Sciences, State University of Semarang. Advisor: Dr. Heny Setyawati, M.Si. Keywords: Development of Gymnastics The background of this research is the lack of development of floor gymnastics (artistic) in Rembang Regency. The purpose of this research is to find out the role of parents, athletes, clubs, communities, koni and the government in the development of floor gymnastics (artistic) in Rembang Regency. This study uses qualitative methods, the subjects of this study are parents of athletes, athletes, coaches, communities, KONI, and the government of Rembang Regency. Data collection techniques use observations, interviews, and documentation. The results of this study found that the role of the athlete's parents entirely allowed their children to follow the sport of floor gymnastics (artistic), but some parents were less assertive in disciplining children. For athletes, the obstacles complained about are about inadequate facilities and infrastructure. From the coach is the difficulty of regenerating athletes due to the lack of willingness from children to train and the lack of strictness of parents, besides that facilities and infrastructure are inadequate. From the community supports the existence of floor gymnastics (artistic), but the lack of socialization makes floor gymnastics (artistic) less desirable. From KONI and the government the lack of direct surveys to training grounds makes this sport less noticed. The conclusion of this study that some parents are less assertive in disciplining children. From athletes obstacles complained about facilities and infrastructure. From the coach is the difficulty of regenerating athletes, the lack of strict parents, inadequate facilities and infrastructure. From the community supports the existence of floor gymnastics, but the lack of socialization makes floor gymnastics (artistic) less desirable. From KONI and the government the lack of direct surveys to the training ground. The advice given by researchers is 1) The parents of athletes are expected to support and support their children to perform better. 2) For athletes more passionate in training and responsible. 3) The coach is expected to remain passionate and patient in training. 4) Society should encourage and participate more in supporting the achievements of athletes. 5) The role of the government is expected to be more optimal in fostering the sport of floor gymnastics (artistic).